2010
DOI: 10.1051/0004-6361/200913353
|View full text |Cite
|
Sign up to set email alerts
|

Gamma rays from annihilations at the galactic center in a physical dark matter distribution

Abstract: We discuss the γ-ray signal to be expected from dark matter (DM) annihilations at the Galactic center. We describe the DM distribution in the Galactic halo, based on the Jeans equation for self-gravitating, anisotropic equilibria. In solving the Jeans equation, we adopted the specific correlation between the density ρ(r) and the velocity dispersion σ 2 r (r) expressed by the powerlaw behavior of the DM "entropy" K ≡ σ 2 r /ρ 2/3 ∝ r α with α ≈ 1.25−1.3. Indicated (among others) by several recent N-body simulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…We stress that the handy SE representation is convenient in analyzing data in several contexts, including: the DM particle annihilation signal expected from the Galactic Center (see Lapi et al 2010a); rotation curves of dwarf and normal spiral galaxies (see Salucci et al 2007); individual and statistical properties of elliptical and spiral galaxies (see Cook et al 2009); strong and weak gravitational lensing (see Lapi et al 2009b), currently observed in clusters (e.g., Zitrin et al 2010) and soon in massive elliptical galaxies (see discussion by Bradač et al 2009); X-ray emission from the intracluster plasma (see Cavaliere et al 2009;Fusco-Femiano et al 2009, Lapi et al 2010b.…”
Section: Results and Commentsmentioning
confidence: 99%
“…We stress that the handy SE representation is convenient in analyzing data in several contexts, including: the DM particle annihilation signal expected from the Galactic Center (see Lapi et al 2010a); rotation curves of dwarf and normal spiral galaxies (see Salucci et al 2007); individual and statistical properties of elliptical and spiral galaxies (see Cook et al 2009); strong and weak gravitational lensing (see Lapi et al 2009b), currently observed in clusters (e.g., Zitrin et al 2010) and soon in massive elliptical galaxies (see discussion by Bradač et al 2009); X-ray emission from the intracluster plasma (see Cavaliere et al 2009;Fusco-Femiano et al 2009, Lapi et al 2010b.…”
Section: Results and Commentsmentioning
confidence: 99%
“…Whilst the finite angular resolution indicates that the observed signal should be finite (unless the density cusp is steeper than r −3/2 ), the signal from the r −1 cusp of an NFW halo should be significantly stronger than that from a cored halo provided that both are normalized locally in the Solar neighbourhood. For example, Lapi et al (2010) find that the NFW halo produces one to two orders of magnitude stronger annihilation signal towards the Galactic centre than the Einasto model with the resolution ranging from ≈ 3 deg 2 to ≈ 100 arcmin 2 .…”
Section: A Family Of Cored Profilesmentioning
confidence: 94%
“…In the following (Sect. 4.3), we shall briefly analyze the behaviour of the so-called astrophysical term J(φ) (e.g., Lapi et al 2010) in the CDM annihilation signal for the dark halo density profile given by our model family. We find that if the dark halo density profile diverges faster than r −1/2 as r → 0, the astrophysical term also formally diverges as φ → 0 -in particular, the r −α cusp (α > 1 2 ) results in J ∈ Θ(φ −(2α−1) ).…”
Section: A Family Of Cored Profilesmentioning
confidence: 99%